Termination of Maritime Boundaries Due to a Fundamental Change of Circumstances - Árnadóttir, Snjólaug (Utrecht Journal of International and European Law, 2016)
An unforeseen fundamental change of circumstances can be invoked to prompt the termination of a treaty, under the customary rule rebus sic stantibus, which is codified in Article 62 of the Vienna Convention on the Law of Treaties (VCLT). The fundamental change must affect the essential basis of the treaty and radically transform obligations still to be performed. Maritime boundaries are agreed upon in accordance with the United Nations Convention on the Law of the Sea and they delimit overlapping maritime entitlements, which are generated by coastal features. Natural occurrences can cause significant and unexpected changes in coastal geography which can affect circumstances essential to a maritime boundary treaty’s conclusion and radically alter the extent of on-going obligations.Treaties establishing boundaries cannot be subject to unilateral termination by virtue of a fundamental change of circumstances because they are excluded under Article 62(2)(a) VCLT. However, the travaux préparatoires of the International Law Commission and relevant case law suggests that the exclusion only covers treaties delimiting territorial boundaries and full sovereignty. Consequently, treaties establishing boundaries to the exclusive economic zone, exclusive fisheries zone and the continental shelf can be subject to termination due to a fundamental change of circumstances.